The Countermeasures Efforts of Illegal Transshipment Impact as a Transnational Crime - Mubaroq, Husni; Putra, Muhammad Haidir Syah (Pancasila and Law Review, 2022)
Abstract The impacts and drawbacks of transshipment, which threaten sustainable development, underscore its classification as a transnational crime. While legal countermeasures are needed to address transshipment crimes in Indonesia, the practice persists due to the necessity of ensuring fish freshness, which involves time-consuming landing processes. Furthermore, the effectiveness of countermeasures is hindered by the lack of a dedicated agency or institution with comprehensive authority to oversee and act against maritime crimes in Indonesian waters. This article examines the relationship between transshipment and transnational crime and proposes a countermeasures framework. The research findings indicate that transshipment is regulated by both international and national laws but qualifies as a transnational crime due to its cross-border impact and its association with other transnational crimes. Recommendations include establishing cooperation between central and regional governments to enhance marine and fisheries governance and implementing a restorative justice mechanism to address fisheries crime cases, such as transshipment, by requiring offenders to compensate for damages and restore fish resources.